A RECREATIONAL VALUATION OF PUBLIC PREFERENCE ON PARK USERS’ WILLINGNESS TO PAY - P. Iamtrakul; K. Teknomo; K. Hokao (International Association of Lowland Technology, 2007)
Public parks provide a numerous benefits and opportunities for community and however, to maintenance of public parks need large amount of local governmental budget. This study investigates park users’ preference on willingness to pay to quantify recreational benefit of public parks. A new assessment method was proposed to verify the consistency of data collection by utilizing the relatively simply technique, we called string method. Based on this approach, a case study of three public parks in Saga city, Japan was established to qualify users’ view that could enable us to evaluate their participation on the improvement of accessibility and attractiveness of park according to community needs. The result indicated that different patterns of recreational travel and activity on park visitation induce in different compensation on public activities’ program. This useful information could be utilized to guide local planning agency to locate suitable policy for public park service improvement.